Molecular detection of Rickettsia infection in field-collected bed bugs. (March 2020) - Potts, R.; Molina, I.; Sheele, J.M.; Pietri, J.E.
Abstract: Bed bugs are now one of the most prevalent human-associated, blood-feeding pests in the urban world, but few studies of their association with human pathogens have been conducted since their resurgence. Here, we used PCR to screen samples of field-collected bed bugs ( Cimex spp.) for the presence of Rickettsia bacteria and we describe the first detection of an uncharacterized Rickettsia in Cimex lectularius in nature. Rickettsia was detected in 5/39 (12.8%) of the bed bug samples tested. In particular, three pools from the USA and two individual insects from the UK were positive for Rickettsia DNA. Sequencing and analysis of a fragment of the citrate synthase gene ( gltA ) from positive samples from each country revealed that the Rickettsia detected in both were identical and were closely related to a Rickettsia previously detected in the rat flea Nosopsyllus laeviceps . Additional experiments indicated that the Rickettsia localizes to multiple tissues in the bed bug and reaches high titres. Attempts were made to infect mammalian cells in culture but these efforts were inconclusive. Our findings suggest that Rickettsia are secondary endosymbionts of bed bugs and have potential implications for both bed bug control and public health. However, further investigation is required to determine the pathogenicity of this Rickettsia, its transmission mechanisms, and its contributions to bed bug physiology.